2016
DOI: 10.7554/elife.18605
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of the ER-shaping proteins atlastin, lunapark, and reticulons to generate a tubular membrane network

Abstract: In higher eukaryotes, the endoplasmic reticulum (ER) contains a network of membrane tubules, which transitions into sheets during mitosis. Network formation involves curvature-stabilizing proteins, including the reticulons (Rtns), as well as the membrane-fusing GTPase atlastin (ATL) and the lunapark protein (Lnp). Here, we have analyzed how these proteins cooperate. ATL is needed to not only form, but also maintain, the ER network. Maintenance requires a balance between ATL and Rtn, as too little ATL activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
247
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(271 citation statements)
references
References 31 publications
24
247
0
Order By: Relevance
“…Yeast and mammalian Lnp proteins preferentially localize to the three‐way junctions of the ER network and it has been suggested that in these organisms Lnp proteins are involved in stabilizing these intersections (Chen et al ., 2012, 2015; Wang et al ., 2016). Although our results showed that AtLNP1 preferentially localizes to ER cisternae rather than junctions, we wanted to determine if AtLNP1 still has a comparable function in stabilizing the overall ER network.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Yeast and mammalian Lnp proteins preferentially localize to the three‐way junctions of the ER network and it has been suggested that in these organisms Lnp proteins are involved in stabilizing these intersections (Chen et al ., 2012, 2015; Wang et al ., 2016). Although our results showed that AtLNP1 preferentially localizes to ER cisternae rather than junctions, we wanted to determine if AtLNP1 still has a comparable function in stabilizing the overall ER network.…”
Section: Resultsmentioning
confidence: 99%
“…This is in contrast to the subcellular localization described for yeast and mammalian Lnp proteins which is rather specific to three‐way junctions; yeast and mammalian Lnp proteins label c . 50% of three‐way junctions, resulting in their stabilization (Chen et al ., 2012; Shemesh et al ., 2014; Wang et al ., 2016). Both AtLNP1 and its animal counterpart can also label ER tubules at higher protein expression levels (Shemesh et al ., 2014; Wang et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations